Аналіз морфологічних характеристик гливи легеневої штаму PLEUROTUS PULMONARIUS (FR.) QUÉL. 2314 ІВК як складових якості грибної сировини - Бандура, Ірина Іванівна; Бандура, Ирина Ивановна; Bandyra, Iryna; Кулик, Аліна Степанівна; Кулик, Алина Степановна; Kulyk, Alina; Гапріндашвілі, Нона Арчилівна; Гаприндашвили, Нона Арчиловна; Haprindashvili, Nona; Макогон, С. В. (ТДАТУ, 2019)
UK: Встановлено, що зростки грибів штаму Pleurotus pulmonarius 2314 IBK на стадії біологічної зрілості досягають на 35% більшої маси, ніж в технологічній. Таким чином, збирання грибів на цьому етапі, за умов швидкої реалізації або використання для переробки, більш доцільне з економічної точки зору. Виявлено, що на стадії технологічної зрілості шапинки більш округлі та темні, а площа їх поверхні на 20% менша, ніж площа шапинок, котрі досягли біологічної зрілості. Визначено, що маса плодових тіл на цих стадіях суттєво не відрізняється, однак, доведено суттєву втрату сухих речовин. Отже, з метою максимального збереження поживної, біологічної цінності, візуальної привабливості під час зберігання у свіжому вигляді та для консервування, рекомендуємо збирати гриби в стадії технологічної зрілості. RU: Установлено, что сростки грибов штамма Pleurotus pulmonarius 2314 IBK на стадии биологической зрелости достигают на 35% большей массы по сравнению с технологической. Таким образом, сбор грибов на этом этапе, в условиях быстрой реализации или использования для переработки, более целесообразен с экономической точки зрения. Выявлено, что на стадии технологической зрелости шляпки более округлые и темные, а площадь их поверхности на 20% меньше площади шляпок, которые достигли биологической зрелости. Определено, что масса плодовых тел на этих стадиях существенно не отличается, однако, доказано значительную потерю сухих веществ. Следовательно, с целью максимального сохранения питательной, биологической ценности, визуальной привлекательности при хранении в свежем виде и для консервирования, рекомендуем собирать грибы в стадии технологической зрелости. EN: Pleurotus pulmonarius or Lung Oyster is commonly known as Phoenix Mushroom, the Indian or Italian Oyster, has a few differences in comparing with Pleurotus ostreatus, for example, the fast substrate colonization, high level of sporulation and short technological cycle. These peculiarities give some economic preferences for mushroom growers in the summer cultivation time. During the study, the mass of clusters Pl. pulmonarius 2314 IBK with biological maturity was on 35% more than for technological stage. The collecting mushrooms in that stage will improve economic benefits in case fast selling or processing. After statistical tests, the significant differences (p < 0,05) for a cap square and a round shape were recognized for the fruit bodies in bio- and technological stages. So younger fruit bodies have Kass = 1, 04 and their square was on 20% less compared with the biological stage. In addition, the color of mushrooms caps with technological maturity was darker. In spite of, the mass of fruit bodies on both stages didn’t have differences, the loss of dry substance was observed. Consequently, growers must collect Pl. pulmonarius 2314 IBK with a technological stage in a reason to keep the nutrition and biological value and the best visual attractions during the storage time. The study revealed a number of changes in the qualitative characteristics of the fruiting bodies of the fungus of the lung strain Pleurotus pulmonarius 2314 during morphogenesis. The fungus growths of this strain at the stage of biological maturity are characterized by a higher mass, therefore, in the case of rapid implementation or use of mushroom raw materials for processing, more economically feasible harvesting of mushrooms is at this stage. In our opinion, it is necessary to further investigate the changes in the biochemical composition of the fruiting bodies and the manifestations of microbiological lesions during the onset of sporulation, in order to obtain undoubted confirmations of this possibility.
Анализ морфологических характеристик вешенки легочной штамма PLEUROTUS PULMONARIUS (FR.) QUÉL. 2314 IBK как составляющих качества грибного сырья
Analysis of morphological characteristics of PLEUROTUS PULMONARIUS 2314 IBK (FR.) QUÉL. as quality characteristics of mushroom raw material
Keywords: глива легенева; грибна сировина; технологічна та біологічна зрілість; площа шапинки; культивування грибів